Epidemiology of Acute Poisonings in Northwestern Syria: A One-Year Study - Zakaria, Wasim; Hmaideh, Ahmad; Alaaraj, Ahmad Musa; Aldan, Nour Alsabah; Alabdullah, Mohammad; Alali, Mohammed Raafat; Abdallah, Abdalhameed; Rashwani, Qusai (Avicenna Journal of Medicine, 2025)
Acute poisoning is a significant public health concern, leading to numerous emergency admissions globally. In northwestern Syria, understanding poisoning epidemiology is essential for targeted prevention efforts. This study examines the causes and demographic characteristics of poisoning cases in the region.The study was conducted over 1 year (July 1, 2022–July 1, 2023) at six northwestern Syrian hospitals supported by humanitarian organizations. The study gathered information from patients aged 14 years and above who suffered from poisoning during the study period.Poisoning cases totaled 172 throughout the study period. Majority of patients were females aged between 14 and 24 (76.7 and 55.2%, respectively), most of them were married (65.1%). Most of the patients identified as housewives among the total patient population (52.9%) and had primary or middle school education. A large majority of the population (77.3%) were smokers while most poisoning incidents (77.3%) were reported in rural camps and villages. The study found oral ingestion as the most common route of poisoning at 88.4% and intentional poisonings made up 86% of all cases. The most prevalent toxic agents causing poisoning cases were drugs, 61.6%, with organophosphorus compounds ranking second, 14.5%. The symptom of vomiting appeared most often during acute poisoning cases (48.8%). The administration of specific antidotes took place in 11.6% of patients who needed hospital admission for 94.8% of these cases. The patients stayed in the hospital for an average duration of 33.1 hours. A total of 76.7% of patients achieved full recovery and 7.6% succumbed to their injuries.Acute poisoning presents as a major health problem across northwestern Syria mostly affecting young married females who live in rural regions. The unusually high number of cases of purposeful poisoning emphasizes the requirement for both psychiatric support and educational programs for the public.
Keywords: acute poisoning; toxic substances; northwestern Syria; public health; intentional poisoning; conflict zones